Cocaine and COVID-19 in ST-Elevation Myocardial Infarction. (22nd April 2022) - Appenzeller, Florian; Gawaz, Meinrad; Müller, Iris
Abstract : Both COVID-19 disease and cocaine consumption have prothrombotic and hypercoagulable effects and are associated with increased risk of cardiovascular events. We report the case of a patient with acute myocardial infarction in the setting of active COVID-19 disease and recent cocaine consumption. We hypothesize that COVID-19 and cocaine synergistically provoke cardiovascular events. Identifying COVID-19 disease and/or cocaine abuse as potential triggers of acute myocardial infarction can be crucial due to distinctive therapeutic consequences.